Biodiversity II : understanding and protecting our biological resources - Reaka-Kudla, Marjorie L.; Wilson, Don E.; Wilson, Edward O. (National Academies Press, 1996)
"The book before you...carries the urgent warning that we are rapidly altering and destroying the environments that have fostered the diversity of life forms for more than a billion years." With those words, Edward O. Wilson opened the landmark volume Biodiversity (1988). Despite this and other such alarms, species continue to vanish at a rapid rate, taking with them their genetic legacy and potential benefits. Many disappear before they can even be identified. Biodiversity II is a renewed call for urgency. This volume updates readers on how much we already know and how much remains to be identified scientifically. It explores new strategies for quantifying, understanding, and protecting biodiversity. The book describes our growing understanding of how megacenters of diversity (e.g., rainforest insects, coral reefs) are formed, maintained, and lost; what can be learned from mounting bird extinctions; and how conservation efforts for neotropical primates have fared. It explores ecosystem restoration, sustainable development, and agricultural impact. Biodiversity II reinforces the idea that the conservation of our biological resources is within reach as long as we pool resources; better coordinate the efforts of existing institutions--museums, universities, and government agencies--already dedicated to this goal; and enhance support for research, collections, and training. This volume will be important to environmentalists, biologists, ecologists, educators, students, and concerned individuals.